The interaction between nirmatrelvir/ritonavir and sirolimus: a case report of a kidney recipient with renal insufficiency and COVID-19 - Yinhua Gong; Dan Shen; Jinfang Shi; Ye Jiang; Jie Gao (Journal of International Medical Research)
Nirmatrelvir/ritonavir is a novel drug combination authorized by the US Food and Drug Administration for the treatment of coronavirus disease 2019 (COVID-19). This report describes the case of a patient with a prior history of kidney transplantation who received nirmatrelvir/ritonavir. In this case, sirolimus use was successfully stopped before nirmatrelvir/ritonavir treatment, and the nirmatrelvir/ritonavir trough concentration was determined. During nirmatrelvir/ritonavir treatment, the sirolimus trough concentration remained stable. This case highlights the risk associated with the concomitant administration of sirolimus and nirmatrelvir/ritonavir. Providers should therefore be cautious when prescribing nirmatrelvir/ritonavir to kidney transplant recipients currently receiving sirolimus, with caution exercised based on creatinine clearance.